2008
DOI: 10.1017/s1751731108002553
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical changes to starch granules during micronisation and extrusion processing of wheat, and their implications for starch digestibility in the newly weaned piglet

Abstract: Two trials were performed to assess changes in the physicochemical properties of precisely processed (micronised v. extruded) wheats, prior to inclusion in piglet diets. The in vitro data obtained were subsequently related to biological responses of newly weaned piglets over 14 days. The effects of the severity of micronisation (Trial 1) or extrusion (Trial 2) on the nutritional value of two wheats (varying in endosperm texture) were examined. Extrusion, in contrast to micronisation, drastically disrupted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…None of the diets contained antibiotic growth promoters or zinc oxide. Two wheat cultivars were used throughout the trials, which were of similar genetic background, identical chemical composition (including protein levels), grown under the same agronomic conditions, but differing in endosperm texture (hard (11·2) and soft (6·3) as measured with the Bran & Luebbe Infra-analyser 260 NIR (4) ). Two batches of soft wheat were used in the research programme; the first batch for trials 1, 2 and 3, the second batch for trials 4 and 5.…”
Section: Piglet Trialsmentioning
confidence: 99%
See 3 more Smart Citations
“…None of the diets contained antibiotic growth promoters or zinc oxide. Two wheat cultivars were used throughout the trials, which were of similar genetic background, identical chemical composition (including protein levels), grown under the same agronomic conditions, but differing in endosperm texture (hard (11·2) and soft (6·3) as measured with the Bran & Luebbe Infra-analyser 260 NIR (4) ). Two batches of soft wheat were used in the research programme; the first batch for trials 1, 2 and 3, the second batch for trials 4 and 5.…”
Section: Piglet Trialsmentioning
confidence: 99%
“…Five piglet trials examined the extent to which in vivo apparent starch digestibility coefficients in the small intestine (taken proportionally at 0·5 and 0·75 along from the gastric pylorus to the ileo-caecal valve) as well as other biological responses (2,4) were affected by diets differing in the source of starch. Starch sources and exact processing conditions used for each trial are summarised in Tables 2, 3 and 4.…”
Section: Piglet Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gelatinization is an irreversible process: water diffuses into the starch granule, hydrogen bonds are disrupted, the granule swells and loses shape, and amylose begins to leach (Holm et al, 1988;Lund & Lorenz, 1984;Moritz et al, 2005;Coral et al, 2009). White et al (2008) reported that the changes in the optical properties of starch can be monitored by the disappearance of 'Maltese crosses' and the disappearance of A-type diffraction patterns in the X-ray diffractograms when wheat granules are submitted to extrusion. The temperature at which starch loses its crystallinity and the material Impact of Particle Size, Thermal Processing, Fat Inclusion, and Moisture Addition on Starch Gelatinization of Broiler Feeds diffuses from the granules is called the "gelatinization temperature".…”
Section: Introductionmentioning
confidence: 99%